Change in phytochemical composition and antioxidant inhibitory activity during processing of Broomcorn millet tea - Phouthaxay, Phonesavanh; Salitxay, Timnoy; Chathaokalor, Doavang; Park, Cheol Ho (Souphanouvong University Journal Multidisciplinary Research and Development, 2017)
This study focused on the evaluation of changes in phytochemical compositions and antioxidant inhibitory activities during the processing of broomcorn millets tea. From the result was showed that Soak-treating of broomcorn millets significantly decreased all of total phenol and tannin contents, and antioxidant activity was compared with raw treatment at p≤0.05, but significantly increased the contents of phenolic acid. In the same case of the steaming treatment were exhibited the contents of total phenol, tannin, reducing power and metal chelating activity significantly decreased, whereas the content of Ferulic acid significantly increased. The process of drying and roasting significantly decrease the contents of total phenolic compounds. Whereas, significantly increased all of total phenol and tannin contents, and antioxidant activity was compared with raw treatment. The total phenolic content of collecting processed millets materials positively correlated with the antioxidant inhibition activities.